Optimization of pain management in cervical dystonia - Marciniec, Michał; Szczepańska-Szerej, Anna; Kulczyński, Marcin; Sapko, Klaudia; Rejdak, Konrad (Journal of Education, Health and Sport, 2018)
Cervical dystonia (CD) is the third most common movement disorder characterized by sustained or intermittent muscle contractions causing abnormal movements, postures, or both. Pain in the course of CD is a frequent symptom reported by the 54.6% - 88.9% of patients, which strongly affects the disability and quality of life, and is the most common reason patients are looking for treatment. Despite the main effect of botulinum toxin (BoNT) is muscle relaxation through the inhibition of the acetylcholine release at the neuromuscular junction, the analgesic effect of BoNT is probably attributed to the acting on central nervous system. Up to 20% of patients discontinue therapy due to treatment failure or adverse effects. Most poor responses are related to suboptimal treatment and a minority to immunoresistance which currently concerns only 0-2,5% of CD cases. In case of confirmed immunoresistance to BoNT-A standard therapy, the use of BoNT-B or alternative BoNT-A is recommended. The currently available management of improving the analgesic efficacy of first-line treatment in patients without immunoresistance includes: the eradication of BoNT adverse events, the determination of individual BoNT dosage, reviewing injections technique with electromyography or ultrasound guidance, the implementation of a rehabilitation program and the applying of the invasive or non-invasive brain stimulation methods. However, due to the lack of evidences from the large, randomized, controlled, clinical trials, an issuance of unambiguous recommendations remains difficult. Further studies on a poor response to BoNT injections and analgesic effects of above methods in the treatment of the CD-related pain are needed.